A escola é a segunda família e a família é a primeira escola:uma arqueogenealogia da parceria entre família e escola - Nascimento, Paulo Henrique Albuquerque do (2017)
This research takes as object of investigation the functioning of a partnership between family and school. To this end, it chooses as a research focus the scenario of public education policy in Brazil, taking as limit some reference documents issued by the Ministry of Education (MEC) and its ways of designating and establishing functions for the school and the family regarding their roles in the field of formal education, but also in their relations with the social environment in a broader way. In addition, it also draws attention to the discursive regimes about the partnership between family and school driven by the academic-scientific scenario, analyzing particularities of dissertations and doctoral theses that touch on this object investigated and problematized, in the most diverse research programs of the country . In fact, this work enables the understanding of the partnership between family and school in the encounter between philosophy and education, in order to produce new effects of meaning for the relationship between these institutions - traditionally allocated as a way of making viable projects of nation -, demarcating also an insertion with the field of the Foucaultian studies. To this end, the conceptual tools of archeology and genealogy, in their couplings in the form of archeogenealogy, work as analytical operators to forge the concept of partnership as a device that encompasses several, sometimes differing, forms and conceptions of the role assigned to the school and the family in our social environment. In order to do so, it also points out that the field of education seems to be a vector through which the partnership between family and school takes on a larger form, but that it also connects and disregards other registers of knowledge as a way of moving its gears, producing changes to, also, what would be the function of the school or the family. Such changes allow, therefore, the production of new fields of knowledge and power relations in their mode of functioning. In this sense, this partnership, through its diffuse, multiple and heterogeneous field of functioning, connects with the strategies of governing the conduct of individuals, in an art of governing, with neoliberal rationality being one of them. In this way, the concept of governmentality will be an ammunition of analysis to examine the ways in which the functioning of this partnership engenders a production of subjectivities and enables a way of maximizing the life and bodies of the subjects. Finally, it points out some discontinuities with regard to the supposedly hegemonic forms of thinking about the relation between family and school, problematizing the ideals of complicity, complementarity and continuity between family and school that are put to this relation in the form of partnership.